The use of telemedicine for ECG interpretation in primary care. (22nd September 2015) - Albouaini, K; Jones, A; Rowe, M; Shtrosberg, S; Egred, M
Abstract : Telemedicine is increasingly used in clinical practice. Broomwell Healthwatch Telemedicine centre was established in 2004 to provide 24-h ECG interpretation, analysis and advice. The centre is staffed by experienced senior cardiac nurses and doctors. Clinical governance and risk management were both involved in this service evaluation and appraisal. Aim: To review the ECG interpretation service over the past 4 years and assess the outcome and advice provided to all referrals made. Methods: A total of 24 541, 12-lead ECG and 805, one-lead ECG received from general practitioner (GP) surgeries between October 2004 and October 2008 was analysed. All ECG were reviewed by two senior cardiac nurses and either a cardiology registrar or a consultant cardiologist. The recommended plans are either: GP assessment, cardiology referral, or emergency department referral. An audit was conducted by Greater Manchester and Cheshire Cardiac and Stroke Network in 29 GP practices, on ECG received between November 2006 and November 2007, to document the level of satisfaction and the number of avoided referrals to secondary care with using this service. Results: Out of the 24 541 12-lead ECG, 15 698 patients were symptomatic. The recommended plans of action were GP assessment: 87.5%, cardiology referral: 6.5%, and emergency department referral: 6%. In the 8843 asymptomatic cases, GP assessment was recommended in 96.3%. The one-lead ECG was performed in 805 cases, GP assessment was advised in 96% of symptomatic patients and 99% of asymptomatic patients. In the satisfaction audit, 60% of the forms were returned (20 practices). Of the 29 GP practices, 17 had their ECG previously reported by their local NHS Trust, which resulted in significant delay in receiving the reports of 1–60 days. With the adoption of the telemedicine service, all ECG were reported within 2 h of their receipt. Satisfaction level questionnaires were filled by 20 GP practices. All were either "very satisfied" or "satisfied" with the service (including the accuracy and speed of ECG interpretation). Secondary care referrals were prevented in up to 65.8% of the total cases (95% CI 61.6% to 65.8%). The extrapolated gross savings derived was in excess of £300 000. Conclusions: Telemedicine and wireless ECG interpretation can enhance the practice by extending the medical consultation from GP practices to a specialist ECG centre. This can ultimately broaden the overall standard of patient care and potentially save time and money.